2023
DOI: 10.1002/trc2.12404
|View full text |Cite
|
Sign up to set email alerts
|

Donanemab exposure and efficacy relationship using modeling in Alzheimer's disease

Abstract: INTRODUCTION:Donanemab is an amyloid-targeting therapy that specifically targets brain amyloid plaques. The objective of these analyses was to characterize the relationship of donanemab exposure with plasma biomarkers and clinical efficacy through modeling.METHODS: Data for the analyses were from participants with Alzheimer's disease from the phase 1 and TRAILBLAZER-ALZ studies. Indirect-response models were used to fit plasma phosphorylated tau 217 (p-tau217) and plasma glial fibrillated acidic protein (GFAP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In this setting, our results were satisfactory for both patients and clinicians, which encourages the use of these criteria to confirm or rule out AD diagnosis. Nevertheless, in this rapidly evolving field, as disease‐modifying therapies advance, further NIA‐AA diagnosis and staging criteria definition are expected [https://aaic.alz.org/diagnostic-criteria.asp], including plasma biomarkers and, hopefully, emerging predictors of treatment response 54–56 . Clearly, a continuous review of AD diagnostic criteria will serve to promote research and to build the bridge between basic science and patient care.…”
Section: Discussionmentioning
confidence: 99%
“…In this setting, our results were satisfactory for both patients and clinicians, which encourages the use of these criteria to confirm or rule out AD diagnosis. Nevertheless, in this rapidly evolving field, as disease‐modifying therapies advance, further NIA‐AA diagnosis and staging criteria definition are expected [https://aaic.alz.org/diagnostic-criteria.asp], including plasma biomarkers and, hopefully, emerging predictors of treatment response 54–56 . Clearly, a continuous review of AD diagnostic criteria will serve to promote research and to build the bridge between basic science and patient care.…”
Section: Discussionmentioning
confidence: 99%
“…It retards progression of the disease and decreases Aβ plaques ( Mintun et al, 2021 ; Reardon, 2023a ) particularly in those with less tau pathology ( Sims et al, 2023 ). Minimal attention has been paid to assessment of potential sex-related differences in the efficacy of donanemab although one paper suggested that sex did not impact on disease progression rates ( Gueorguieva et al, 2023 ). As in the case of lecanemab, the risk of ARIA was greater in APOE4 carriers compared with non-carriers.…”
Section: Is There Evidence Of Sex-related Differences In Response To ...mentioning
confidence: 99%